Male Infertility, Impaired Sperm Motility, and Hydrocephalus in Mice Deficient in Sperm-Associated Antigen 6 - Sapiro, Rossana (American Society for Microbiology, 2002)
Gene targeting was used to create mice lacking sperm-associated antigen 6 (Spag6), the murine orthologue of Chlamydomonas PF16, an axonemal protein containing eight armadillo repeats predicted to be important for flagellar motility and stability of the axoneme central apparatus. Within 8 weeks of birth, approximately 50% of Spag6-deficient animals died with hydrocephalus. Spag6-deficient males surviving to maturity were infertile. Their sperm had marked motility defects and was morphologically abnormal with frequent loss of the sperm head and disorganization of flagellar structures, including loss of the central pair of microtubules and disorganization of the outer dense fibers and fibrous sheath. We conclude that Spag6 is essential for sperm flagellar motility and that it is important for the maintenance of the structural integrity of mature sperm. The occurrence of hydrocephalus in the mutant mice also implicates Spag6 in the motility of ependymal cilia.